Pengaruh Hasil Belajar Membaca Pada Hasil Pembelajaran Berbasis Teknik Mind Mapping - Alya Rohali; Fida Chasanatun; Ibadullah Malawi (Prosiding Konferensi Ilmiah Dasar, 2022)
The purpose of this study is to find out the influence of the reading learning outcomes on learning outcomes based on mind mapping techniques for elementary school students. Reading is one of the language skills that must be mastered by students. Whereas the mind mapping technique is one of the learning techniques by mapping ideas or ideas creatively. This research is quantitative research with ex-post facto approach by examining events that have taken place previously. The sample in this study was class IV E students at MIN 2 Madiun City, totaling 37 students. Sampling using a purposive sampling technique. The technique of collecting data on reading learning outcomes uses a test technique with an instrument in the form of Year-End Assessment questions. The data analysis technique used is descriptive analysis to test the hypothesis with the help of Microsoft Excel program.  The results of this study are as follows: 1)There is an influence of students’ reading learning outcomes on learning outcomes based on mind mapping techniques of class IV. 2) The average learning outcome of the experimental class that applies mind mapping techniques is higher than the control class, the average learning outcome of the experimental class is 81.62 while the average learning outcome of the control class is 77.02. Thus, the results of this study indicate that mind mapping techniques can have an influence on students' reading learning outcomes.